Vegetative cycle, ant mutualism and leaf characteristics of Coccoloba gigantifolia trees at a new site in central Amazonia - Baur, Peter; Silva, Clevânio Crosa da; Baur, Philipp; Peres, Rubins da Silva; Dario, Iuri Stefano Negrisiolo (Flora, 2022)
Basic features and inflorescences of Coccoloba gigantifolia were described in 2019 only, after first documentation by academia 1982 at Borba, Madeira river basin, one of two main sites so far. Here we report about vegetative life cycle, leaf and other characteristics of more than 10 trees from a new site, east of the Mamori Lake, at 70 km distance and not directly influenced by the inundation of the Madeira basin. The tree was known there and named by local Mura indigenes and caboclos, but no use is known. All trees, from juvenile saplings to subadult and mature trees, showed an extreme growth form of sympodial monochasium. Also, all trees grew on hillocks in more fertile soil than the surroundings as indicated by high soil conductivity. The habitat suggests previous termite nests on or independent of stubs. The tree is facultatively associated with ants, very convergent to Cecropia species. There were pronounced heterophyllous differences regarding trichomes and stomata density, chlorophyll contents per area, dimensional and anatomical features. The general leaf phenotypes and chlorophyll contents indicated Mg-deficiency and a huge shade leaf responded overnight to magnesium addition with a 3-fold increased, more uniform leaf chlorophyll content. The chlorophyll contents per area and maximum potential photochemical quantum efficiency of PS II of three leaves of a young tree were low but constant. Retention of water by trichomes and anatomical features were compared to glabrous Coccoloba uvifera. With exceptionally huge leaves of C. gigantifolia growing in the understory, the tree is ecologically challenged in an environment low in nutrients which is indicated by the rare existence, ant mutualism and other adaptations.